The Effectiveness Of Regulatory Socialization In Supporting The Use Of MSMEs Products As Hotel Amenities And Its Impact On Guest Trust - Kashuri, Mohamad (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This research explores the effectiveness of regulatory socialization in supporting the use of MSMEs natural cosmetic and medicinal products as hotel amenities, as well as its impact on guest trust. The survey results of hotel industry players indicate that the adoption of MSME products is still low, with the main obstacles being a lack of understanding of regulations and product costs. This study concludes that increasing business and regulatory literacy through integrated programs and providing certified e-catalogs of products can enhance the competitiveness of MSMEs and strengthen Indonesia's image as a wellness tourism destination. This research provides an innovative contribution to the empowerment strategies of MSMEs in the hotel and tourism industry.